Pengembangan Asesmen Literasi Kimia pada Materi Hukum-Hukum Dasar Kimia dan Stoikiometri - Apri Yolla Mulya Sartika; Eka Yusmaita (Edukimia, 2020)
This chemistry literacy assessment instrument developed because of recent challenge toward student learning achievement evaluation so it could not only grade student’s cognitive ability in term of understanding and memorizing, but also will grade the application of students’ concept to face any problems. The availability of the chemistry literacy assessment instrument consists of various aspects, such as content, context, High Order Learning Skills (HOLS), and attitude. These aspects are expected to answer those challenges. This study aims to produce a proper and right chemistry literacy assessment toward fundamental law of chemistry and stoichiometry topic based on content validity value and questions numbers, reliability grade, difficulty level and chemistry literacy question differentiator level. This study is the development type, which is Model of Educational Reconstruction (MER) design. The clarification of a test instrument on empirical study was done toward three chemistry and education experts (lecturer and teacher). The instrument used was chemistry literacy question which consists of seven discourse question, then expanded into 15 questions. The result showed that content validity value of the designed chemistry literacy assessment could be categorized as valid.